Identification and coping strategies of nursing disputes in the Emergency Department (急诊科护理纠纷识别及应对策略) - WANG Jing (王晶); LI Shuyue (李淑悦); YANG Yuwei (杨雨薇); CAO Wenjie (曹文杰); LI Han (李涵); QIAO Xinli (乔新立); REN Yaxing (任亚星) (中西医结合护理)
The risk of medical disputes is relatively high in the Emergency Department. Issues of nurse-patient communication, triage, nursing records, quality of care are influencing factors of nursing risk. Identification of high-risk patients, high-risk nurses, high-risk working periods and optimizing the hospital visiting constitute the precondition of reducing risk in emergency care. By implementing risk management, improving nursing level and social positive interaction, the incidence of nursing risk events can be reduced and the safety of patients, medical staff and family members can be ensured. (急诊科是医疗纠纷的高风险科室。护患沟通、分诊、护理记录、护理质量是引发护理风险的相关因素, 准确识别高危患者、高危护士、高危时段, 优化就诊环节是降低急诊护理风险的前提。通过实施纠纷风险管理、提高护理水平、社会良性互动, 有助于降低护理风险事件的发生率, 保证患者及医护等人员的安全。)